Muricauda ochracea sp. nov., isolated from a tidal flat in the Republic of Korea. Issue 8 (28th August 2020) - Kim, Dongjun; Yoo, Yeonjae; Khim, Jong Seong; Yang, Dongmin; Pathiraja, Duleepa; Choi, In-Geol; Kim, Jae-Jin
Abstract : A yellowish-brown-coloured bacterium, designated strain JGD-17 T, was isolated from a tidal flat of Janggu-do, Garorim bay, Taean-gun, Chungcheongbuk-do, Republic of Korea. Cells were Gram-stain-negative, aerobic, non-flagellated and long-rod-shaped. Growth was observed at 20–45 °C (optimum, 25–30 °C), at pH 6.0–10.0 (9.0) and with 1–5 % (w/v) NaCl (1–3 %). Results of 16S rRNA gene sequence analysis indicated that strain JGD-17 T was closely related to Muricauda nanhaiensis SM1704 T (96.1 %), Muricauda olearia CL-SS4 T (95.0 %), Muricauda beolgyonensis BB-My12 T (94.9 %), Muricauda marina H19-56 T (94.7 %) and Muricauda indica 3PC125-7 T (94.5 %). The ranges of values for the average nucleotide identity and digital DNA–DNA hybridization analyses with related strains were 71.3–74.1 % and 16.9–18.2 %. The genomic DNA G+C content was 41.1 mol%. Phylogenetic analysis using the neighbour-joining method showed that strain JGD-17 T formed a clade with Muricauda nanhaiensis SM1704 T, Muricauda lutaonensis CC-HSB-11 T, Muricauda lutea CSW06 T and Muricauda pacifica SM027 T . The major fatty acids were iso-C15 : 0 (26.9 %), iso-C15 : 1 G (19.5 %) and iso-C17 : 0 3-OH (12.7 %). The predominant respiratory quinone was menaquinone-6. The polar lipids were phosphatidylethanolamine, an unidentified aminolipid, an unidentified phospholipid and two unidentified lipids. On the basis of phylogenetic, phenotypic and chemotaxonomic characteristics, strain JGD-17 T represents a novel species within the genus Muricauda, for which the name Muricauda ochracea sp. nov. is proposed. The type strain is JGD-17 T (=KCTC 72732 T =KACC 21486 T =JCM 33817 T ).